Guarded Evaluation: An Algorithm for Dynamic Power Reduction in FPGAs - Ravishankar, Chirag (University of Waterloo, 2012)
Guarded evaluation is a power reduction technique that involves identifying sub-circuits (within a larger circuit) whose inputs can be held constant (guarded) at specific times during circuit operation, thereby reducing switching activity and lowering dynamic power. The concept is rooted in the property that under certain conditions, some signals within digital designs are not "observable" at design outputs, making the circuitry that generates such signals a candidate for guarding. Guarded evaluation has been demonstrated successfully for custom ASICs; in this work, we apply the technique to FPGAs. In ASICs, guarded evaluation entails adding additional hardware to the design, increasing silicon area and cost. Here, we apply the technique in a way that imposes minimal area overhead by leveraging existing unused circuitry within the FPGA. The LUT functionality is modified to incorporate the guards and reduce toggle rates. The primary challenge in guarded evaluation is in determining the specific conditions under which a sub-circuit's inputs can be held constant without impacting the larger circuit's functional correctness. We propose a simple solution to this problem based on discovering gating inputs using "non-inverting paths" and trimming inputs using "partial non-inverting paths" in the circuit's AND-Inverter graph representation. Experimental results show that guarded evaluation can reduce switching activity by as much as 32% for FPGAs with 6-LUT architectures and 25% for 4-LUT architectures, on average, and can reduce power consumption in the FPGA interconnect by 29% for 6-LUTs and 27% for 4-LUTs. A clustered architecture with four LUTs to a cluster and ten LUTs to a cluster produced the best power reduction results. We implement guarded evaluation at various stages of the FPGA CAD flow and analyze the reductions. We implement the algorithm as post technology mapping, post packing and post placement optimizations. Guarded Evaluation as a post technology mapping algorithm inserted the most number of guards and hence achieved the highest activity and interconnect reduction. However, guarding signals come with a cost of increased fanout and stress on routing resources. Packing and placement provides the algorithm with additional information of the circuit which is leveraged to insert high quality guards with minimal impact on routing. Experimental results show that post-packing and post-placement methods have comparable reductions to post-mapping with considerably lesser impact on the critical path delay and routability of the circuit.
Keywords: Field-programmable gate arrays; Power optimization; low-power design; logic synthesis; technology mapping; Electrical and Computer Engineering